Nature-Based Physical Activity and Hedonic and Eudaimonic Wellbeing: The Mediating Roles of Motivational Quality and Nature Relatedness - Jenkins, Matthew; Lee, Craig; Houge Mackenzie, Susan; Hargreaves, Elaine Anne; Hodge, Ken; Calverley, Jessica (Frontiers in Psychology, 2022)
The current study evaluated the degree to which nature-based physical activity (NPA) influenced two distinct types of psychological well-being: hedonic well-being and eudaimonic well-being. The type of motivation an individual experiences for PA, and the extent to which individuals have a sense of relatedness with nature, have been shown to influence the specific type of psychological well-being that is experienced as a result of NPA. However, the role of these two variables in the relationship between NPA and psychological well-being has not been examined. Thus, this study assessed the potential mediating influence of (1) motivational quality and (2) nature relatedness on the relationships between NPA and hedonic and eudaimonic well-being, respectively. Participants (N = 263) completed an online survey assessing hedonic and eudaimonic well-being, NPA, intrinsic motivation, autonomous extrinsic motivation, and nature relatedness. Data were analysed using Partial Least Squares Structural Equation Modelling. Results showed that motivational quality and nature relatedness both fully mediated the relationships between NPA and hedonic and eudaimonic well-being. Specifically, intrinsic motivation positively mediated the relationship between NPA and hedonic well-being. Autonomous extrinsic motivation and nature relatedness positively mediated the relationship between NPA and eudaimonic well-being. These findings suggest that the associations between NPA and eudaimonic well-being and hedonic well-being, respectively, are driven by different mechanisms relating to an individual’s (1) underlying motivation and (2) sense of connection to nature. These findings suggest that promoting distinct types of well-being (hedonic versus eudaimonic) through NPA requires distinct approaches. Emphasising enjoyment, pleasure, and positive kinaesthetic experiences within NPA may be more conducive to hedonic well-being, while highlighting opportunities for connecting with nature or experiencing valued outcomes of NPA may be more conducive to eudaimonic well-being.